The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s13337-015-0255-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of Orf virus from natural outbreaks in goats of Assam

Abstract: Outbreaks of contagious ecthyma (caused by a Parapox virus) in goats were investigated in 6 districts of Assam, a north eastern state of India. Diagnosis of the disease was carried out employing both standard virological as well as molecular methods. Four representative isolates from different places were selected for phylogenetic analysis. The major envelop protein (B2L) of Orf virus was targeted for molecular analysis. The sequencing and phylogenetic analysis of the selected sequences at nucleotide level rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Clinical signs of orf infection was used to identify animals with CE. Typical Orf virus CPE was observed in LT and MDCK cells as reported previously [4,19,26]. These include ballooning, rounding and degeneration of cells as early as 3 days post inoculation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Clinical signs of orf infection was used to identify animals with CE. Typical Orf virus CPE was observed in LT and MDCK cells as reported previously [4,19,26]. These include ballooning, rounding and degeneration of cells as early as 3 days post inoculation.…”
Section: Discussionsupporting
confidence: 81%
“…Cell culture method is a time consuming method used for viral isolation [4,27]. However, PCR technique has been used as a faster and more effective method of Orf virus detection [14].…”
Section: Discussionmentioning
confidence: 99%
“…during the months of August to January. Similar outbreaks of orf had been reported from different parts of India viz., Uttarakhand (Venkatesan et al, 2011), Assam (Bora et al, 2015), Uttar Pradesh (Kumar et al, 2014), Rajasthan (Mann et al, 2014).The scab samples were collected from different areas of the outbreak. A total of 9 scab samples were collected and processed.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2010, ORFV has rapidly increased in many countries, especially in China and India, and is now the predominant PPV species in farmed sheep [51][52][53][54][55][56]. It indicated that under the selective pressure of the optimal gene pattern by going through the selective bottleneck the ORFV eventually became the dominant species during the 2010 -2018 outbreak.…”
Section: Discussionmentioning
confidence: 99%